Stone sculpture A: new evidence for early iconography in the northern section of the Callejón de Huaylas - Querevalú Ulloa, José Samuel (2017)
This research pretends to discuss new data on the iconography belonging to Callejón de Huaylas —district of Santa Cruz, province of Huaylas— during the Formative period. The study shows the description, analysis and correlation of the fragment of a frieze, which has been called Stone sculpture A, must be associated to a monumental architectural sites. Also, you can see contemporary characteristic iconographic elements in other surrounding areas such as north-central coast and mountains.